2020
DOI: 10.1021/acsinfecdis.0c00317
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Single-Cell Imaging Reveals Accelerating Lipid Peroxyl Radical Formation in Escherichia coli Triggered by a Fluoroquinolone Antibiotic

Abstract: The formation of reactive oxygen species (ROS) induced by bactericidal antibiotics has been associated with a common, nonspecific mechanism of cellular death. Herein, we report real-time single-cell fluorescence studies on Escherichia coli stained with a fluorogenic probe for lipid peroxyl radicals showing the generation of this form of ROS when exposed to the minimum inhibitory concentration (MIC) and 10× MIC of the fluoroquinolone antibiotic ciprofloxacin (3 and 30 μM, respectively). Single-cell intensity–ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 69 publications
(138 reference statements)
3
25
0
Order By: Relevance
“…We speculate that α-tocopherol may be less potent in E. coli than in eukaryotes due to potentially limited scavenging potential and uptake. Intriguingly, a recent study developed a lipophilic antioxidant different from α-tocopherol and showed that it prevented lipid peroxidation and fluoroquinolone-induced cell death in E. coli 40 ; together with our results, this observation suggests a varied landscape of chemical compounds that could attenuate lipid peroxidation and, in doing so, mitigate antibiotic lethality.…”
Section: Resultssupporting
confidence: 80%
“…We speculate that α-tocopherol may be less potent in E. coli than in eukaryotes due to potentially limited scavenging potential and uptake. Intriguingly, a recent study developed a lipophilic antioxidant different from α-tocopherol and showed that it prevented lipid peroxidation and fluoroquinolone-induced cell death in E. coli 40 ; together with our results, this observation suggests a varied landscape of chemical compounds that could attenuate lipid peroxidation and, in doing so, mitigate antibiotic lethality.…”
Section: Resultssupporting
confidence: 80%
“…This result indicated that ROS played an important role in the antimicrobial process of K18S4 against S. aureus. Among the possible ROS related antibacterial mechanisms, the increase of intracellular ROS level after the peptide polymer entered the bacteria could cause the damage of bacterial membrane due to membrane lipid peroxidation 57,58 . Characterization on the morphological changes of bacteria by transmission electron microscope (TEM) and scanning electron microscope (SEM) showed membrane lysis and cytoplasm outflow of S. aureus, E. coli and V. anguillurm after treatment with K18S4 (Fig 5i , 5j).…”
Section: Resultsmentioning
confidence: 99%
“…44 Of note is also the fact that the analysis of the mechanisms of action for well-established antibacterial drugs revealed their ability to generate oxidative stress in bacteria, which increases/complements their target-specific modes of action. [84][85][86] Applications of gold in therapy have long roots in mankind's history. 87 However, it was not until Robert Koch's observation of the bacteriostatic activity of K[Au(CN) 2 ] followed by the introduction of salvarsan by Paul Ehrlich that metals entered into the antibacterial field following the scientific method.…”
Section: Manuel Arruebomentioning
confidence: 99%
“… 44 Of note is also the fact that the analysis of the mechanisms of action for well-established antibacterial drugs revealed their ability to generate oxidative stress in bacteria, which increases/complements their target-specific modes of action. 84–86 …”
Section: Introductionmentioning
confidence: 99%